Sequential Ecological Relay of a BALIMONT Multi-Strain Probiotic Platform for Weight Management and Metabolic Environment Modulation - Ziraoui, Anas; Ellsworth, Vivian; Hayes, Cameron (International Journal of Agriculture and Food Sciences Research, 2026)
We evaluated a BALIMONT multi-strain probiotic platform composed of Bacillus coagulans ATCC 7050, Bifidobacterium animalis ATCC 27536, and Lactobacillus plantarum DSM 20174, and we integrated the original formulation dataset with currently available published evidence relevant to probiotic-based weight management. The platform used a 1:1:1 viable-count ratio and a sequential ecological-relay design in which B. animalis and L. plantarum were pre-incubated in a B. coagulans cell-free metabolite filtrate before final blending with B. coagulans spore powder. In the original comparative dataset, six-month viable-count retention reached 85.2%, versus 52.0% for a same-strain direct-mix comparator. In vivo, B. coagulans first reduced free oxygen from 5.2 mg/L to 0.8 mg/L and shifted the proximal intestinal redox potential from +120 mV to −180 mV, followed by jejunal/ileal enrichment of L. plantarum and distal-colon enrichment of B. animalis. In obese mice, the medium and high doses reduced body weight by 12.3% and 15.7%, body-fat percentage by 18.5% and 22.4%, and colonic short-chain fatty acids by 58% and 72%, respectively, relative to the model pattern reported in the source dataset. Published human studies and meta-analyses further support the plausibility of probiotic-mediated improvement in visceral fat, body weight, insulin resistance, and microbiota-related metabolic markers. Together, these data support BALIMONT as a process-defined probiotic platform for metabolic-environment modulation and justify further randomized human validation.